Drivers of pCO2 variability in two contrasting coral reef lagoons: The influence of submarine groundwater discharge. Issue 4 (15th April 2014) - Cyronak, Tyler; Santos, Isaac R.; Erler, Dirk V.; Maher, Damien T.; Eyre, Bradley D.
Abstract The impact of groundwater on pCO2 variability was assessed in two coral reef lagoons with distinct drivers of submarine groundwater discharge (SGD). Diel variability of pCO2 in the two ecosystems was explained by a combination of biological drivers and SGD inputs. In Rarotonga, a South Pacific volcanic island, 222Rn‐derived SGD was driven primarily by a steep terrestrial hydraulic gradient, and the water column was influenced by the high pCO2 (5501 µatm) of the fresh groundwater. In Heron Island, a Great Barrier Reef coral cay, SGD was dominated by seawater recirculation through the sediments (i.e., tidal pumping), and pCO2 was mainly impacted through the stimulation of biological processes. The Rarotonga water column had a higher average pCO2 (549 µatm) than Heron Island (471 µatm). However, pCO2 exhibited a greater diel range in Heron Island (778 µatm) than in Rarotonga (507 µatm). The Rarotonga water column received 29.0 ± 8.2 mmol free‐CO2 m−2 d−1 from SGD, while the Heron Island water column received 12.1 ± 4.2 mmol free‐CO2 m−2 d−1. Over the course of this study, both systems were sources of CO2 to the atmosphere with SGD‐derived free‐CO2 most likely contributing a large portion to the air‐sea CO2 flux. Studies measuring the carbon chemistry of coral reefs (e.g., metabolism and calcification rates) may need to consider the effects of groundwater inputs on water column carbonate chemistry. Local drivers of coral reef carbonate chemistry such as SGD may offer more approachable management solutions to mitigating the effects of ocean acidification on coral reefs.